An Analysis of Deixis on Comment Speech By Indonesian Diplomat in United Nation (PBB) 75th General Assembly Meeting 2020 - Minkhatunnakhriyah Minkhatunnakhriyah; Didin Nuruddin Hidayat; Alek Alek (VELES Voices of English Language Education Society, 2021)
Deixis is a human language phenomenon in which particular expression referential depends on context use (Williams, 2019). By knowing deixis, a speaker knows alternate reference words depending on the interlocutor, places and time conversation takes place. The study investigates deixis and its context used by diplomats and representatives from Indonesia, Silvany Pasaribu of human rights cases of Vanuatu and Papua. This study's data source was the comment speech of an Indonesian diplomat, consisting of three types of deixis based on Levinson's theory. The video was collected from YouTube. Further, to analyse the data through several processes, the researchers firstly collected all deictic expressions found in transcription, classified the deictic word into each category of deixis. The result of this study shows thirty five deixis from comment speech of Indonesian diplomat.  There were twenty three personal deixis consisting of a first, second, and third person, seven spatial deixis, and five temporal deixis. Person deixis generally be delivered by person grammatical type, which replaces personal pronoun encode like community, appropriate names, and the individual pronoun compound. Spatial or place deixis based on result which expresses by the speaker on their speech were location. Temporal deixis is used to the pointing of time context speech. Further research is suggested to analyze all kinds of deixis, such as social deixis and its context.